Analisis Performa PLTS Off Grid Untuk Sistem Desalinasi Metode Osmosis Terbalik - Supriyono, Supriyono; Purwiyanto, Purwiyanto; Aji Girawan, Bayu; Setia Pribadi, Joko; Santoso, Agus (Infotekmesin, 2023)
Bondan Hamlet is a hamlet in Kampung Laut District, Cilacap. One of the community's problems is the lack of clean water and the PLN electricity network. In 2020, a desalination facility named Sidesi Mas will be built in Bondan Hamlet with a capacity of 240 liters/hour and using the reverse osmosis principle. The energy source for desalination uses a solar power plant (PLTS). Desalination management requires economic analysis, especially in determining the selling price of desalinated water. The cost of producing desalinated water can be calculated using the Cost of energy (CoE) value of the PLTS or the costs incurred to produce electrical energy per 1 kWh. To get the PLTS CoE, this article discusses a simulation to analyze the performance of PLTS desalination systems with Homer software. Homer performs analytical calculations based on a location input, solar energy potential, capacity, and costs of PLTS components as well as electrical load data. The simulation results show that PLTS energy production is 535 kWh/year, the CoE value is IDR 21,975/kWh and the production cost for producing clean water is IDR 183.13/liter.